2020
DOI: 10.1186/s12877-020-01752-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of dysphagia among nursing home residents in eastern China: a cross-sectional study

Abstract: Background Dysphagia is a common health care problem and poses significant risks including mortality and hospitalization. China has many unsolved long-term care problems, as it is a developing country with the largest ageing population in the world. The present study aimed to identify the prevalence and risk factors of dysphagia among nursing home residents in China to direct caregivers towards preventative and corrective actions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 46 publications
1
42
0
11
Order By: Relevance
“…Third, suspected dysphagia was defined based on the EAT-10 in the questionnaire survey and not on a clinical diagnosis. Some recent studies using the EAT-10 questionnaire for the screening of suspected dysphagia among elderly people reported that the reliability and validity of the questionnaire were excellent [ 33 , 57 59 ]. However, if the questionnaire was used with psychiatric patients, the reliability and validity of the questionnaire might be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Third, suspected dysphagia was defined based on the EAT-10 in the questionnaire survey and not on a clinical diagnosis. Some recent studies using the EAT-10 questionnaire for the screening of suspected dysphagia among elderly people reported that the reliability and validity of the questionnaire were excellent [ 33 , 57 59 ]. However, if the questionnaire was used with psychiatric patients, the reliability and validity of the questionnaire might be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other developing countries, China has a larger ageing population and relatively less developed long-term care systems, with different policies and standards. 6 In 2019, there were 204,000 nursing homes, with a total of 7.75 million beds. 7 Only 1.5% to 2.0% of people aged 65 and over living in nursing homes, which is a lower institutional care rate compared with 4% to 8% in Western countries.…”
Section: Nursing Home Characteristics In Chinamentioning
confidence: 99%
“…Third, suspected dysphagia was de ned based on the EAT-10 in the questionnaire survey and not on a clinical diagnosis. Some recent studies using the EAT-10 questionnaire for the screening of suspected dysphagia among elderly people reported that the reliability and validity of the questionnaire were excellent [34,[58][59][60]. However, if the questionnaire was used with psychiatric patients, the reliability and validity of the questionnaire might be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…There are ve response categories with an associated score (l=always, 2=often, 3=sometimes, 4=seldom, and 5=never). The GOHAI score is computed by summing the scores of the 12 responses, and the highest score (60) indicates excellent oral health.…”
Section: Questionnaire Surveymentioning
confidence: 99%